Penulisan Naskah Program Berkah Islami di Kompas TV Jawa Tengah - Istiqomah Sheyla Al Kautsar; Yanuar Luqman (Interaksi Online, 2020)
Television is still ranked as the highest mass media consumed by the public. The development of the increasingly rapid television industry also invited local television to take part in filling Indonesia's glass screens. One of the local television stations in Central Java, especially Semarang, which still exists on air until now is Kompas TV in Central Java. Kompas TV Jawa Tengah became a television station that featured news programs and information that were accurate, fast, informative, trusted, educating and inspiring. The making of the Berkah Islami program stems from the lack of religious programs that raise adab and sunnah regarding minor issues in human daily life based on the Koran and Hadith which are discussed lightly and can be applied so that they are easily understood by the public. So that it becomes a challenge for the script writer to pour his ideas into a piece of paper that is presented in accordance with good writing procedures for television programs, so that the content presented in a program can be a reference and make it easier for all parties involved in the execution process both in front or behind the scenes to produce shows that are interesting, informative, and can educate the public. The "Berkah Islami" program is presented in a talkshow format which is present to give knowledge to the public about adab and sunnah in Islam and its application in daily life based on the Koran and hadith for thirteen (13) different themes in each episode. The Berkah Islami Program airs every Sunday at 05.00 WIB on Kompas TV Central Java with a duration of 21-24 minutes and airs from September 1 to November 23 2019. Work on the production of the work program "Berkah Islamic" program involves four production teams and one marketing person . This report focuses on describing the tasks of the script writer from the production, production, and post-production stages along with the obstacles and solutions. Through the Islamic Blessings program it is expected that the script writer can pour his ideas into a writing as a document that can be a reference for the director and work relatives (crew) in completing the production of television programs, in providing informative religious shows and educating Muslim communities in applying the customs and sunnah taught by Islam thus brings blessing.